High-performance NIR-sensitive fused tetrathienoacene electron acceptors. Issue 6 (22nd January 2020) - Wang, Wei; Lu, Heng; Chen, Zhenyu; Jia, Boyu; Li, Kejia; Ma, Wei; Zhan, Xiaowei
Abstract : Fused tetrathienoacene electron acceptors, F8IC1 and F10IC1, were synthesized and compared with thienothiophene-based F6IC. The organic solar cells based on F8IC1 and F10IC1 achieved higher efficiencies than those of the F6IC-based cells. Abstract : New electron-donating fused-ring cores based on tetrathienoacene were designed, with which new NIR-sensitive fused-ring electron acceptors, F8IC1 and F10IC1, were synthesized. Compared with the thieno[3, 2- b ]thiophene-based counterpart F6IC, F8IC1 and F10IC1 show heavily elevated HOMO and slightly elevated LUMO levels, bathochromic absorption spectra with reduced optical bandgaps, and enhanced electron mobilities. Paired with the polymer donor material PTB7-Th, the organic photovoltaic devices based on F8IC1 and F10IC1 show synchronous enhancement of open-circuit voltage, short-circuit current and fill factor. The single-junction cells based on F8IC1 and F10IC1 achieve efficiencies of 10.7% and 12.3%, respectively, surpassing those of the F6IC-based control cells (7.00%).